Aktywni obywatele – analiza porównawcza osób działających w organizacjach trzeciego sektora w Polsce - Masłyk, Tomasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The degree of citizen participation in Poland as a key factor responsible for the development of third sector organizations is relatively low compared to countries of developed democracy. Despite political, economic or social difficulties, from year to year there is a gradual increase in non-governmental organizations representing the sphere. The purpose of this article is to present the characteristics of active citizens working in various third sector organizations with regard to their socio-demographic profiles. The analysis was performed for the total active people based on data from studies carried out in the 2013Social Diagnosis.
Active citizens – a comparative analysis of people working in the organizations of the third sector in Poland
Keywords: third sector; active citizenship; civil society; Social Diagnosis